The Driving Factors for Recidivism of Former Terrorism Convicts in Socio-Legal Perspective - Ali Masyhar; Ali Murtadho; Ahmad Zaharuddin Sani Ahmad Sabri (Journal of Indonesian Legal Studies, 2023)
The phenomenon of recidivism among former terrorism convicts presents a complex challenge within the socio-legal context. This study aims to explore the driving factors behind the recurrence of terrorism-related offenses among previously incarcerated individuals. By employing a socio-legal perspective, the research examines the interplay of social and legal factors that contribute to the re-engagement of former terrorism convicts in illegal activities. Drawing on existing literature and empirical data, this paper identifies various key factors, including societal stigma, socio-economic struggles, and deficiencies in the legal system. The study underscores the importance of comprehensive policies that address both social and legal dimensions to effectively prevent and address recidivism in the terrorism context. By understanding and addressing these driving factors, policymakers and practitioners can develop more targeted and nuanced interventions to facilitate successful rehabilitation and reintegration while safeguarding national security and promoting social cohesion.